2018
DOI: 10.1182/bloodadvances.2017014860
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional impact of recurrent S1PR1 mutations in mantle cell lymphoma

Abstract: Key Points S1PR1 mutations are present in 7.8% of patients with MCL and are significantly more frequent at relapse. S1PR1 mutations reduce expression of the S1PR1 receptor, which mediates migration towards the tissue-to-blood egress factor S1P in MCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Sphingosine 1 phosphate receptors (S1PR1-5) represent a family of G protein-coupled receptors that bind the sphingolipid (S1P) and influence migration and survival pathways in a variety of cell types; S1PRs are emerging as biomarkers in B cell lymphomas [3][4][5][6] and B cell development [7]. Our prior work, which demonstrated S1PR1 expression in a subset of classic Hodgkin lymphoma cases [8], has recently been supported by others [9].…”
Section: Introductionmentioning
confidence: 85%
“…Sphingosine 1 phosphate receptors (S1PR1-5) represent a family of G protein-coupled receptors that bind the sphingolipid (S1P) and influence migration and survival pathways in a variety of cell types; S1PRs are emerging as biomarkers in B cell lymphomas [3][4][5][6] and B cell development [7]. Our prior work, which demonstrated S1PR1 expression in a subset of classic Hodgkin lymphoma cases [8], has recently been supported by others [9].…”
Section: Introductionmentioning
confidence: 85%
“…High surface S1PR1 levels facilitate mobilization of B-cells from these niches into the circulation. MCL cells express high surface levels of S1PR1 [48], and low S1PR1 expression contributes to retention within microenvironmental niches [54], likely promoting tumor cell survival. Consistently, our results showed that S1PR1 is expressed on both JeKo-1 and REC-1 cells, albeit at higher levels on REC-1 cells, as shown previously [48], and its attenuation enhanced the capacity for JeKo-1 and REC-1 cells to adhere to stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, retention of MCL in the supportive microenvironment could represent a residual reservoir of cancer cells linked to relapse. It remains to be determined whether S1P 1 inactivating mutations can reduce ibrutinib sensitivity in MCL [32]. However, chemotherapeutic resistance is associated with enhanced adhesion of MCL to the stroma and ibrutinib increases expression of S1P 1 , while decreasing CCR7 levels in chronic lymphocytic leukaemia.…”
Section: Role Of S1p In Tumour Neovascularisation and Metastasismentioning
confidence: 99%